Teacher Empowerment Strategy to Improve the Quality of Education at SMAN 1 Palangka Raya - Yeprina Prihatini Asie; Eka Mutmainnah; Septina Wijayanti; Aslamiah Aslamiah; Celia Cinantya (Universitas Negeri Yogyakarta, 2026)
This descriptive qualitative study, carried out at SMAN 1 Palangka Raya, employs observations, interviews, and documentation to explore strategies for teacher empowerment. Data processing entails collection, reduction, presentation, and verification. From processing data, the following research results were obtained: 1) The teacher empowerment strategy starts with analyzing training needs from the Education Report Document to enhance teacher competency. The school organizes development programs and regular meetings aligned with its goals. Initiatives include workshops, self-development opportunities, reflection on practices, and learning communities. The principal supervises these activities through classroom observations to monitor implementation and ensure ongoing effectiveness. 2) Empowering teachers at SMAN 1 Palangka Raya improves the quality of education through a variety of teaching methods, technology skills, and a culture of reflection. Support for training and collaboration among teachers is crucial for professional development. Recognition of achievements increases motivation and fosters a positive work environment, which enhances students' learning experiences. Teacher empowerment significantly contributes to student success, thereby enhancing the reputation of SMAN 1 Palangka Raya as an institution that produces competent graduates.